Taxonomic notes on the genus Spinosodus Breuning & de Jong, 1941 (Coleoptera, Cerambycidae) with a generic and specific synonym - Shuai Zhao; Ting Qin; Guanglin Xie; Wenkai Wang (ZooKeys)
Taxonomic notes on the genus Spinosodus Breuning & de Jong, 1941 are presented. The genus Bulbolmotega Breuning, 1966 is synonymized with Spinosodus, and Bulbolmotega sumatrensis Breuning, 1966 is recognized as a junior synonym of Spinosodus spinicollis Breuning & de Jong, 1941. Additionally, Spinosodus is redescribed, and S. rufomaculatus Breuning, 1973 is formally reported from China, Vietnam, Thailand, and India for the first time.